Sudove zastosuvannâ aktìv Konstitucìjnogo sudu Ukraїni âk džerel admìnistrativnogo prawa - Rešota, Volodimir (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Acts of the Constitutional Court of Ukraine occupy a special place in the system of sources of administrative law. It is underlined in the article that their status is not regulated by Ukraine’s legislation, which leads to a misunderstanding of their position and correlation with other sources of administrative law. In 2017, the Ukrainian parliament adopted a new edition of the law “On the Constitutional Court of Ukraine”. It is argued in the article that this law introduced some new features to the legal system of Ukraine, for example, a constitutional complaint, which allows any person to submit a complaint against any law he or she may regard to be unconstitutional.This law also defines all types of acts that the Constitutional Court may adopt. The author of the article states that there is no common position concerning the place of the acts of Ukraine’s Constitutional Court in the system of sources of administrative law. Some scholars argue that these acts cannot be regarded as sources of law, as they do not contain a legal norm within, while others insist that these acts have obligatory status and must be fulfilled by all subjects of law in Ukraine. It is argued in the article that acts of the Constitutional Court of Ukraine have huge impact on legal norms and thus they should be treated as sources of law. It is stressed that not all acts of the Constitutional Court should be treated as sources of administrative law, but only those which influence administrative law norms or provide an interpretation of them.The paper stresses that article 83 of the “On the Constitutional Court of Ukraine” law provides all types of acts the Constitutional Court of Ukraine may adopt, namely: decisions, conclusions, determinations, security orders and court rulings concerning other issues not connected with constitutional proceedings.The article emphasizes that the decision of the Constitutional Court of Ukraine regarding the constitutionality of laws of Ukraine and other acts of the Ukrainian parliament, acts of the President of Ukraine, acts of the Cabinet of Ministers of Ukraine, and acts of the Supreme Council of the Autonomous Republic of Crimea and decisions on the official interpretation of the Ukraine’s Constitution should be included in the sources of administrative law. It is stressed in the article that among all conclusions of the Constitutional Court of Ukraine only conclusions concerning the compliance of current international treaties of Ukraine with Ukraine’s Constitution may be regarded as sources of administrative law of Ukraine.
Keywords: The Constitutional Court of Ukraine; source of administrative law; judicial decision; legal position